A high-Q acoustic filter based on programable electromechanical Fano resonance. (15th May 2023) - Zhang, Yumin; Mo, Di; Han, Xue; Xu, Jiawen; Wang, Chunqi; Huang, Lixi; Wu, Keming
Graphical abstract: Abstract: Fano resonance with a sharp and ultra-narrow asymmetrical spectral profile is formed by interfering a background mode by a local mode, which is widely found in numerous physical areas and serves as a bedrock for architecting functional metamaterials and constructing selective filters for physical waves. However, it requires subtle geometries and accurate mechanical properties for generating a local resonance to realize Fano resonance at a desired frequency, which challenges its widely applications. Here, we report an electromechanical Fano resonance delivered by an electromechanical diaphragm shunted by a multiple-branch resonant circuit (SEMD). The local resonance of the SEMD is induced by the electrical circuit, which removes the constraints of subtle geometries and mechanical properties design and allows digitally programing the Fano resonance through coding MOSFET switches to select a preset circuit branch. A Lumped theoretical model is used to analyze circuit effects, with verification by experiments in a one-dimensional waveguide, showing programing of three key parameters, the frequency, Q factor and extinction ratio (ER), of the electromechanical Fano resonance. The frequency of perfect sound absorption (null reflection) digitally assigned in a frequency range of [158.5 Hz 1486.75 Hz] is experimentally demonstrated, equivalent to a wavelength-to-thickness ratio range of [31.6 0.30], regarding the equivalent thickness of the SEMD. The Q factor of the SEMD, indexing the selectivity, can be tuned up to 145 in experiments and over 6000 theoretically, giving the half-bandwidth less than 0.2 Hz. The extinction ratio (ER) reaches 30 dB in experiments whereas 60 dB in predictions which means the circuit can totally change the acoustic response of the mechanical diaphragm. Due to features of real-time programmability, broadband tunability and mechanical properties and geometries independence, the SEMD with an electromechanical Fano resonance would be a superior platform to fulfill the envisaged manipulation of acoustics waves in a digital manner.